Data platform and urban data services on private cloud - Vassilev, Vassil; Virdee, Bal Singh; Ouazzane, Karim; Mariyanayagam, Dion; Sowinski-Mydlarz, Viktor; Rabka, Monika; Maosa, Herbert; Radu, Sorin (2022)
This paper presents the result of a pilot project of London Metropolitan University, aiming at developing a set of urban data services in support of the local communities in several boroughs of the city of London. They are targeting the health and well-being of the citizens by analyzing different types of information from a number of data sources – environmental sensors, geolocation information, and models of the urban infrastructure. Unlike the complex government projects covering large urban areas, which require significant resources and typically involve large service providers operating public clouds, our project targets local communities with limited capabilities by utilizing the concept of a private cloud running on commodity infrastructure within their reach. By employing a number of proven data technologies, software tools, and AI methods the project delivers a comprehensive picture of urban life. The first phase of the project reported here focuses on outdoor and indoor pollution, which are the keys for addressing many local community activities such as environment protection, urban planning, local transport, communal housing, and social services within the area.